2021
DOI: 10.1111/1365-2664.14055
|View full text |Cite
|
Sign up to set email alerts
|

Third and fourth trophic level composition shift in an aphid–parasitoid–hyperparasitoid food web limits aphid control in an intercropping system

Abstract: 1. Understanding how resource diversification affects ecological interactions, food web structure and ecosystem functioning is essential in both fundamental and applied ecology. While plant diversification strategies (either in-field or around-field) are often proposed in agricultural landscapes as practices to improve the biological control of herbivores by natural enemies, results remain variable and unsure.2. Here, we studied the effect of an in-field diversification practice (the intercropping of leguminou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 84 publications
1
5
0
Order By: Relevance
“…and Pachyneuron sp. [ 76 ] Similar to our results, a recent study found a different hyperparasitoid species composition when more plant resources were added (leguminous plants) intercropped with cereals [ 27 ]. This change in parasitoid composition could be explained although the SV treatment had a patchily distributed, non-persistent and vegetational cover (less plant density), but with a higher species richness, being composed mostly of wild gramineous plants and weeds introduced from other plant families, such as Malvaceae and Asteraceae.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…and Pachyneuron sp. [ 76 ] Similar to our results, a recent study found a different hyperparasitoid species composition when more plant resources were added (leguminous plants) intercropped with cereals [ 27 ]. This change in parasitoid composition could be explained although the SV treatment had a patchily distributed, non-persistent and vegetational cover (less plant density), but with a higher species richness, being composed mostly of wild gramineous plants and weeds introduced from other plant families, such as Malvaceae and Asteraceae.…”
Section: Discussionsupporting
confidence: 88%
“…Indeed, neutral, and even negative, effects of natural enemy diversity on the abundance of pests have been observed [ 25 , 26 ]. Increasing plant diversity may also increase potential negative interactions like intraguild predation or hyperparasitism, resulting in lower pest suppression [ 25 , 26 , 27 , 28 ]. It is necessary to better understand the effects of increasing plant diversity on ecosystem functioning by quantifying the functional role of the interactions within insect communities to evaluate the habitat provisioning role in biological control [ 27 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that a high functional dispersion would ‘dilute’ the relative importance of the plants producing nectar exploited by predators (and having a positive mass effect) among other plants providing unexploited resources. High dispersion probably also favoured the fourth trophic level, which includes hyperparasitoids, thereby disrupting aphid control by primary parasitoids, as shown for crop diversification (Jeavons et al, 2021). Indeed, Campbell et al (2012) previously reported that rates of flower visitation by parasitoids were highest in stands of plants bearing only flowers with short corollas and that these rates were much lower in plant stands bearing flowers with more diverse traits, due to higher levels of competition with bumblebees and hoverflies.…”
Section: Discussionmentioning
confidence: 98%
“…The authors explained these contrasting results by the use of non-species-speci c cues, as kairomones and oral resources, that may have antagonistic effect. Indeed, companion plants and semiochemicals may attract intra-or extraguild predators as well as parasitoids and hyperparasitoids (Jeavons et al 2022), decreasing the e ciency of targeted natural enemies, or even attract other pest species or antagonists such as ants (Hambäck et al, 2021;Heil, 2015). In the same line, alternative food resources may act as a diversion, being preferred over the target pest by natural enemies, therefore decreasing biological control (Brown and Mathews 2007).…”
mentioning
confidence: 99%